Transition of Learning between High and Fast Spike Skills in Volleyball - Muhammad Salih, Muhammad Salih (International Journal of Psychosocial Rehabilitation, 2020)
The researcher spoke in the introduction of the research on highlighting the role and importance of the property of the effect of the transfer of learning, which plays a role in the economy of time in the stages of learning and reducing the effort exerted and hence the importance of research in the need to find new ways and ways to help students to learn the skill of spike, which is one of the skills that the student finds himself Obliged in its learning despite its difficulty on beginners and the need to recognize the impact of the transfer of learning in teaching the skill of spike multiplication, so the question of the form of the problem that is whether the student's learning to spike in its various forms plays an effective role in improving the evaluation of the performance of the spike or not either the goal of the lake W was first in recognizing the impact of the education of spikes in its various forms on the evaluation of the performance of the high and fastspike of volleyball and secondly in helping to develop a method for the best method in the education of spike without going out of the program of the college, but the imposition of research was to learn different types of spike achieves a positive transition in Evaluation of the performance of the high and fastspike and fast and the research sample of the second stage students in the Faculty of Physical Education and Sports Sciences - University of Baghdad - University of Baghdad (80) students and the time period for the conduct of the research between 26/2/2018 and 11 April 2018 on The internal hall in the Faculty of Physical Education and Sports Sciences / University of Baghdad (Al-Jadriya) the research method used by the researcher was the experimental method of the system of equal groups because it is the most appropriate method, as the sample of (80) students is divided into four groups by (20) students for each group of students of the second stage In the Faculty of Physical Education and Sports Sciences University of Baghdad for the academic year 2017- 2018, where the first group learned division (d) fast and then high spike while learning the second group Division(b) high spike and then fast and learning the third group division (and) beating The researcher found that the second experimental group, Division B, which learned the high spike multiplication and then the fastspike, had a moral effect in evaluating the performance of the high-hit crush, as the learning of fastspikes had a positive effect in the high spike learning (the first group and the second best of the fourth group in the high spike) and did not appear to learn the spike beating with a positive effect in the beating. The researcher recommended that the learning of the high spike first and then followed by learning fastspike as a new method of gradualization in the learning of spike and utilizing similar motor skills in volleyball, which help to speed up learning for its effectiveness in transmitting the impact of positive learning and add the education of fastspike of various types and introduce it in the educational program followed by the college.